French companies and public procurement in Africa - (:unkn) unknown (My University, 2019)
Contractual relationships between french-speaking african countries and french companies in the public procurement sector are formed under a complex network of national, regional and international rules breaking away from the historical french legal and administrative model. These relationships are maintained through ill-defined hybrid contracts that draw from public and international contractual laws and practices. They are integrated into legal and financial frameworks balancing profitability, public interests, environmental and social matters.
Keywords: African Research